Magnesium chloride/aluminum dichlorhydroxide mixed catalyst for low energy curing of durable press fabrics with low formaldehyde release - Reeves, Wilson A.; Mohd Salleh, Naimah (Sage Publications, 1984)
Scoured and bleached cotton printcloth was treated with a methylated DMDHEU using magnesium chloride, aluminum dichlorhydroxide, and three mixtures of mag nesium chloride and aluminum dichlorhydroxide as catalyst. The purpose of the study was to produce durable press fabrics that release a minimum of formaldehyde under cure conditions that conserve energy. Curing was done for 20, 60 and 180 seconds at 140, 170, and 200°C. Wrinkle recovery values and durable press ratings increased as the amount of aluminum dichlorhydroxide increased in the catalyst systems. The lowest formaldehyde release came from fabrics cured at 140°C and catalyzed with the mixed catalyst containing 0.2% aluminum dichlorhydroxide, but this system failed to produce ad equate wrinkle recovery. For low energy consumption, low formaldehyde release, and high durable press properties the best combination was the mixed catalyst con taining 0.4% aluminum dichlorhydroxide with 1.0% magnesium chloride and a 20 second cure at 170°C.